Factors that Influence Behavior in Maintaining Cleanliness Reproductive Organs When Menstruation at SMP PGRI 58 Tanjung Morawa, Deli Serdang - Safitri, Mey Elisa (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
The habit of keeping cleanliness during menstruation, including thecleanliness of reproduction organ, plays an important role in the status of healthbehavior in order to avoid the problem of the function of the reproduction organin a woman. The purpose is to avoid infection in the reproduction organ whicheventually will lower the quality of her life. The objective of the research was toanalyze the influence of knowledge, attitude, availability of facilities, mother’srole, teacher’s role, and peer’s role on behavior of keeping the cleanliness ofreproduction organ during menstruation in the female students of SMP PGRI 58Tanjung Morawa, Deli Serdang District, in 2013.The type of the research was descriptive analytic with cross sectionalapproach. The population was all 391 female students of SMP PGRI 58 TanjungMorawa, and 194 werevused as the samples. The data were analyzed by using ChiSquare test and multiple logistic regression tests.The result of the research showed that female students who kept theircleanliness of their reproduction organs during menstruation were 49%. Therewas the influence of the variable of knowledge in cleanliness of reproductionorgan during menstruation (p=0.005), the correlation of mother’s role withmenstruation (p=0.010), and peer’s role in sharing experiences aboutmenstruation (p=0.007) on behavior of keeping cleanliness of reproduction organduring menstruation. On the other hand, attitude, availability of facilities, andteacher’s role did not have any correlation and influence on behavior of keepingcleanliness of reproduction organ during menstruation.It is recommended that parents and the management of the school increasethe behavior of their female students about cleanliness of reproduction organs byimproving health socialization of teenager reproduction about cleanliness duringmenstruation. The socialization is conducted through health education, peereducation program, and extracurricular activities.